PENDAFTARAN TANAH WAKAF: URGENSI DAN PROSEDURNYA - Harianto, Asis; Riancana, Resti; Djamal, Riniarty (Jurnal Yustisiabel, 2025)
One of the important steps in providing legal certainty and protection for waqf assets is the registration of waqf land. However, there are still many waqf lands that have not been registered, which can cause disputes and changes in function that are not in accordance with the purpose of waqf. The analysis of the urgency and procedures for registering waqf land in Indonesia is the purpose of this article. This study uses a normative juridical with a statutory and conceptual approach. Data were collected through a literature study that includes legal regulations, academic journals, and books. Registration of waqf land is very important for the community because it provides legal certainty, prevents disputes, ensures that the land is used according to its intended use, and facilitates the management and development of waqf assets. Registered waqf land is also easier to get assistance from the government and avoids unauthorized changes in function. Registration of waqf land begins with the wakif giving land to the nazhir through the waqf pledge deed official (PPAIW) to issue a waqf pledge deed. After that, the PPAIW and nazhir register the waqf land with the Ministry of ATR/BPN through the Regency/City Land Office.